1999
DOI: 10.1111/j.1749-6632.1999.tb09415.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Activates the p21/WAF1/Cip1 Gene Promoter through the Sp1 Sites

Abstract: Trichostatin A (TSA), a specific histone deacetylase inhibitor, induces histone hyperacetylation and modulates the expression of some genes. We examined the effects of TSA on MG63 cells. TSA induced growth arrest and expression of the p21/WAF1/Cip1 protein. A close correlation between the level of histone acetylation and induction of the p21/WAF1/Cip1 protein was detected. Using several mutant p21/WAF1/Cip1 promoter fragments, mutation of either of two Sp1 sites at -82 or -69 of the p21/WAF1/Cip1 promoter redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
96
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 8 publications
13
96
0
Order By: Relevance
“…Critically, the principal mechanism of growth inhibition appeared to be induction of apoptosis rather than cell cycle arrest, supporting further a diminished role for p21 (waf1/cip1) in mediating the antiproliferative e ects. Thus, although we cannot exclude a contribution from transcriptional upregulation of p21 (waf1/cip1) by 1a,25(OH) 2 D 3 and NaB, via speci®c NaB-response elements (Pace et al, 2000;Iowa et al, 1999), we believe the contribution at the dose used in the current study, is minimal.…”
Section: Discussionmentioning
confidence: 83%
“…Critically, the principal mechanism of growth inhibition appeared to be induction of apoptosis rather than cell cycle arrest, supporting further a diminished role for p21 (waf1/cip1) in mediating the antiproliferative e ects. Thus, although we cannot exclude a contribution from transcriptional upregulation of p21 (waf1/cip1) by 1a,25(OH) 2 D 3 and NaB, via speci®c NaB-response elements (Pace et al, 2000;Iowa et al, 1999), we believe the contribution at the dose used in the current study, is minimal.…”
Section: Discussionmentioning
confidence: 83%
“…It has been proposed that p21 WAF1/Cip1 could be one of the better candidates for gene-regulating chemotherapy or chemoprevention, because it is mutated less frequently than p53 gene in human common cancers (Hollstein et al, 1991;Chedid et al, 1994;Li et al, 1995) and its induction by HDAC inhibitors is mediated by a p53-independent pathway (Nakano et al, 1997;Sowa et al, 1999;Huang et al, 2000;Han et al, 2001). It is, therefore, important to understand the induction mechanism of p21 WAF1/Cip1 by HDAC inhibitors in chemotherapy or chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the induction of p21 WAF1/Cip1 by these stimuli could be regulated by various signal transduction pathways that mediate cell growth, differentiation, and stress response (Hu et al, 1999;Lee et al, 2000;Mitsuuchi et al, 2000). Also, it has been demonstrated that p21 WAF1/Cip1 induction by HDAC inhibitors was mediated via Sp1 sites through Sp1 family transcription factors, Sp1 and/or Sp3 (Nakano et al, 1997;Sowa et al, 1999;Huang et al, 2000;Han et al, 2001). However, the detailed signal transduction pathways involved in p21 WAF1/Cip1 gene regulation by HDAC inhibitors still remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous chromatin immunoprecipitation data showed that Zac1 might be recruited to the p21 promoter through the Sp1 sites (13), similar to HDAC1 for this promoter (34). We wished to determine whether HDAC1 was involved in the regulation of the p21 gene via p53, Zac1, or both combinations.…”
Section: Physical Interaction Between Zac1 and Hdac1mentioning
confidence: 99%